AN ULTRASOFT X-RAY FLARE FROM 3XMM J152130.7+074916: A TIDAL DISRUPTION EVENT CANDIDATE - Lin, Dacheng; Maksym, Peter W.; Irwin, Jimmy A.; Komossa, S.; Webb, Natalie A.; Godet, Olivier; Barret, Didier; Grupe, Dirk; Gwyn, Stephen D. J. (The Astrophysical journal, 2015)
ABSTRACT We report on the discovery of an ultrasoft X-ray transient source, 3XMM J152130.7+074916. It was serendipitously detected in an XMM-Newton observation on 2000 August 23, and its location is consistent with the center of the galaxy SDSS J152130.72+074916.5 (z = 0.17901 and dL = 866 Mpc). The high-quality X-ray spectrum can be fitted with a thermal disk with an apparent inner disk temperature of 0.17 keV and a rest-frame 0.24-11.8 keV unabsorbed luminosity of ∼5 × 1043 erg s−1, subject to a fast-moving warm absorber. Short-term variability was also clearly observed, with the spectrum being softer at lower flux. The source was covered but not detected in a Chandra observation on 2000 April 3, a Swift observation on 2005 September 10, and a second XMM-Newton observation on 2014 January 19, implying a large variability (>260) of the X-ray flux. The optical spectrum of the candidate host galaxy, taken ∼11 years after the XMM-Newton detection, shows no sign of nuclear activity. This, combined with its transient and ultrasoft properties, leads us to explain the source as tidal disruption of a star by the supermassive black hole in the galactic center. We attribute the fast-moving warm absorber detected in the first XMM-Newton observation to the super-Eddington outflow associated with the event and the short-term variability to a disk instability that caused fast change of the inner disk radius at a constant mass accretion rate.